2017
DOI: 10.3233/jad-170809
|View full text |Cite
|
Sign up to set email alerts
|

Mental States in Moving Shapes: Distinct Cortical and Subcortical Contributions to Theory of Mind Impairments in Dementia

Abstract: Impaired capacity for Theory of Mind (ToM) represents one of the hallmark features of the behavioral variant of frontotemporal dementia (bvFTD) and is suggested to underpin an array of socioemotional disturbances characteristic of this disorder. In contrast, while social processing typically remains intact in Alzheimer's disease (AD), the cognitive loading of socioemotional tasks may adversely impact mentalizing performance in AD. Here, we employed the Frith-Happé animations as a dynamic on-line assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 94 publications
0
48
2
Order By: Relevance
“…The thalamus exhibits dense connections to the hypothalamus which may also potentially influence changes in body composition through neuroendocrine inputs, and has been previously implicated in changes in eating behavior in FTD and BMI in ALS . Changes in body composition (android: gynoid ratio and VAT area) also correlated to atrophy of the cerebellum, which has again been implicated in overeating behavior in FTD, and a range of autonomic, cognitive, emotional functions, and reward processing …”
Section: Discussionmentioning
confidence: 97%
“…The thalamus exhibits dense connections to the hypothalamus which may also potentially influence changes in body composition through neuroendocrine inputs, and has been previously implicated in changes in eating behavior in FTD and BMI in ALS . Changes in body composition (android: gynoid ratio and VAT area) also correlated to atrophy of the cerebellum, which has again been implicated in overeating behavior in FTD, and a range of autonomic, cognitive, emotional functions, and reward processing …”
Section: Discussionmentioning
confidence: 97%
“…Regarding decoding processes, studies in AD using photographs of faces expressing basic emotions have yielded inconsistent results (for a review, see Klein-Koerkamp et al, 2012), with some studies reporting a deficit (Kumfor et al, 2014;Laisney et al, 2013) and others not (Bucks & Radford, 2004;Fernandez-Duque et al, 2009). Links are frequently found between affective ToM and other cognitive functions, especially flexibility, working and/or episodic memory, and inhibition (Castelli et al, 2011;Fliss et al, 2016;Ramanan et al, 2017;Synn et al, 2018). As a result, the ToM impairments of patients with AD are often attributed to cognitive disorders, and commensurate with the severity of the disease, rather than to disturbed emotional processes (Dermody et al, 2016, Kumfor et al, 2014Ramanan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Very few tasks assessing affective ToM have involved reasoning processes. Using a visual task that minimized the overall cognitive demand, a recent study highlighted a deficit in affective mental state attribution in patients with AD (Synn et al, 2018). Supplementary analyses taking into account scores on a vocabulary task showed that the patients' performances on the affective ToM question of the task improved to be then similar to controls.…”
Section: Introductionmentioning
confidence: 99%
“…Structural and functional abnormalities of the cerebellum are present in numerous developmental and acquired neurological conditions, such as developmental dyslexia, autism spectrum disorders, alcohol‐related brain damage, movement disorders (eg, Friedreich ataxia, Parkinson disease, Huntington disease), dementia (eg, Alzheimer disease [AD], dementia with Lewy bodies, frontotemporal dementia), and psychiatric disorders . The contribution of the cerebellum to motor coordination and motor planning is well known, but many studies have downplayed its involvement in other domains despite the mounting evidence over the past 30 years (eg, language, social cognition, interoception).…”
mentioning
confidence: 99%